SIKAP AFEKTIF PENYULUH TERHADAP WEBSITE CYBER EXTENSION SEBAGAI SUMBER INFORMASI PENYULUHAN PERTANIAN DI KABUPATEN KARANGANYAR - Dzakiroh, Dewi; Wibowo, Agung; Ihsaniyati, Hanifah (AGRITEXTS: Journal of Agricultural Extension, 2017)
This research aimed to examine the relationship between the factors establishing the extension agents’ attitude to website cyber extension and the  extension agents’ affective attitude to website cyber extension as the source of agricultural extension information and to analyze the difference between Civil Servant Extension Agent’s and the THL-TBPP Extension agent’s affective attitudes to website cyber extension as the source of agricultural extension information. The fundamental method employed in this research was a descriptive quantitative method. The location of research in Karanganyar  Regency. The sample was taken using proportionate stratified random sampling method.The data was gotten by using questionnaire to 64 respondents passed observation, interview, and documentation. Data analysis that’s useRankSpearman’s and Mann-Whitney U tests. Considering the result of research, it could be seen that  majority respondents were 46-55 years old and graduated from formal education at S1 (graduate) level, the non-formal education level in very lowcategory, their personal experience in lowcategory, and other significant people’s effect was substantial. Meanwhile, the agricultural extension agent’s affective attitude to the quality of website cyber extensionin formation and design was good, and the extension agent’s affective attitude to the quality of website cyber extension use quality was poor. Considering the result of analysis, it could be found that there was a significant relationship between age, non-formal education, personal experience and other significant people’s effect, and the extension agent’s affective attitude to website cyber extension, but there was no significant relationship between formal education and the extension agents’ affective attitude to website cyber extension. Considering the result of Mann Whitney U test, it could be seen that there was a difference between Civil Servant Extension Agent’s and the THL Extension agent’s attitudes to website cyber extension as the source of agricultural extension information.